Morfoanatomia foliar de três espécies de Bauhinia L. E Schnella autimouta (Aublet) Wunderlin (Cercideae - Fabaceae), e Análise citogenética de Buhinia cheilantha (Bong) Steud. e Bauhinia ungulata L. - Pereira, Larísse Bianca Soares (2016)
Bauhinia and Schnella are representatives genres of Bauhiniinea subtribe in Brazil, where they have greater diversity. The genus Bauhinia is pantropical, with about 160 species, of which 57 occur in Brazil, of which 35 are endemic. Schnella is a neotropical group with 47 species, 33 found in Brazil, with 17 endemic. The species of these genera are popularly used in traditional medicine, especially against diabetes and known as "pata-de-vaca" due to the shape of their leaves bilobates. Furthermore, Schnella is also used against diarrhea syphilis and other South American countries. This study aimed to a study of leaf morphoanatomy the three species of Bauhinia: Bauhinia cheilantha (Bong.) Steud., B. pentandra (Bong.) Vogel ex Steud., B. ungulata L., and Schnella outimouta (Aublet) Wunderlin, complemented by a cytogenetic study B. cheilantha and B. ungulata as a subsidy to the group's taxonomy. Leaf anatomy studies were conducted on fresh samples and fixated and also in dried samples after hydration, following the usual techniques for anatomy, analyzed and shown by optical microscopy. Cytogenetic studies were conducted in the roots of an individual of each species, the banding technique, with the fluorochrome 4 ', 6-diamidino-2-phenylindole (DAPI) and Chromomycin (CMA), which form the bands DAPI-/CMA+ or DAPI +/CMA-. It was observed that these species share the following characters: bilobates leaves, dorsiventral mesophyll, papillose hypophyll, stomata anomocytic the level of the epidermis, distal pulvinus, and trichomes. It was observed that Schnella outimouta distinguished from the species Bauhinia to be hypostomatic with adaxial epidermal glabra, midrib with two collateral bundles and circular petiole. The species of Bauhinia are amphistomatic with pillous epidermis on one or both surfaces, with boat shaped glands, midrib with a single bundle and petiole with lateral projections. In cytogenetic analyzes B. cheilantha and B. ungulata showed symmetrical karyotypes, with 2n = 28, without presenting DAPI+ bands, so devoid of heterochromatic regions rich in AT. On the other hand, rich in GC subterminal bands were observed in the chromosomal short arms in the karyotypes of the two species. However, B. ungulata differentiated itself by having six terminals bands CMA+/DAPI- while B. cheilantha presented only four bands. The use of staining with specific base fluorochromes CMA and DAPI, allowed a clear differentiation chromosome between the two species, although they are difficult taxonomic delimitation in vegetative stage. The results provide cytogenetic and anatomical and distinctive parameters, which are inexistent, for the species of Bauhinia, particularly in regard to the epidermis anatomy and its attachments, vascularization of the medrib, the shape of margins and petioles that were diagnostic for Bauhinia and Schnella corroborating the actual treatment for Bauhiniinae that separete species of Bauhinia and Schnella.